RETRACKTED: ANALISIS KESULITAN BELAJAR SISWA KELAS XII IPA SMA NEGERI 9 MANDAU DURI PADA MATERI REPRODUKSI SEL TAHUN AJARAN 2021/2022 - Ifat Rizah; Mellisa Mellisa (Bioilmi: Jurnal Pendidikan, 2023)
The revocation note is entitled "Revocation [Analisis Kesulitan Belajar Siswa Kelas XII IPA SMA Negeri 9 Mandau Duri Pada Materi Reproduksi Sel]” which has been published in Bioilmi: Jurnal Pendidikan Volume 9, Number 2, 2023. There has been a violation of the professional code of ethics, namely double submission in another journal and has been published in the Biology and Education Journal Volume 2, Number 2, 2023. Here is the link the journal; https://journal.uir.ac.id/index.php/baej/article/view/11064. The retraction of the article by the Editor has been approved by the author. This is important to do because plagiarism violations occur. We as managers of Bioilmi: Jurnal Pendidikan, hope that this incident of violation of the code of ethics can be resolved.